Polyneuritis cranialis related to SARS-CoV-2 infection: a case report - Gradišnik, Peter; Osterc Koprivšek Andreja; Rus, Miha; Golli Tanja; Damjan, Hermina (Acta Medico-Biotechnica, 2023)
Purpose: Polyneuritis cranialis (PNC) is a less known regional variant of Guillain-Barré syndrome and has rarely been described in children. Here, we report a case of an adolescent, who became perilously ill following severe acute respiratory syndrome-coronavirus 2 infection. Case report: A 15-year-old boy presented with acute multiple cranial nerve palsies. The presence of GQ1b antibodies and nerve conduction studies confirmed the diagnosis of PNC. The patient was treated with plasmapheresis and intravenous immunoglobulins, but clinical improvement was gradual and very slow. Conclusion: PNC is a rare and severe neurologic condition that can be triggered by coronavirus infection.